The impact of a physician's recommendation and gender on informed decision making: A randomized controlled study in a simulated decision situation - Anna Lea Meinhardt; Marie Eggeling; Ulrike Cress; Joachim Kimmerle; Martina Bientzle (Wiley, 2021)
Abstract Objective This study examined the influence of physicians' recommendations and gender on the decision‐making process in a preference‐sensitive situation. Methods N = 201 participants were put in a hypothetical scenario in which they suffered from a rupture of the anterior cruciate ligament (ACL). They received general information on two equally successful treatment options for this injury (surgery vs physiotherapy) and answered questions regarding their treatment preference, certainty and satisfaction regarding their decision and attitude towards the treatment options. Then, participants watched a video that differed regarding physician's recommendation (surgery vs physiotherapy) and physician's gender (female vs male voice and picture). Afterwards, they indicated again their treatment preference, certainty, satisfaction and attitude, as well as the physician's professional and social competence. Results Participants changed their treatment preferences in the direction of the physician's recommendation (P < .001). Decision certainty (P < .001) and satisfaction (P < .001) increased more strongly if the physician's recommendation was congruent with the participant's prior attitude than if the recommendation was contrary to the participant's prior attitude. Finally, participants' attitudes towards the recommended treatment became more positive (surgery recommendation: P < .001; physiotherapy recommendation: P < .001). We found no influence of the physician's gender on participants' decisions, attitudes, or competence assessments. Conclusion This research indicates that physicians should be careful with recommendations when aiming for shared decisions, as they might influence patients even if the patients have been made aware that they should take their personal preferences into account. This could be particularly problematic if the recommendation is not in line with the patient's preferences.